2022
DOI: 10.3390/diagnostics12020407
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Modalities of Non-Alcoholic Fatty Liver Disease: From Biochemical Biomarkers to Multi-Omics Non-Invasive Approaches

Abstract: Non-Alcoholic Fatty Liver Disease (NAFLD) is currently the most common cause of chronic liver disease worldwide, and its prevalence is increasing globally. NAFLD is a multifaceted disorder, and its spectrum includes steatosis to steatohepatitis, which may evolve to advanced fibrosis and cirrhosis. In addition, the presence of NAFLD is independently associated with a higher cardiometabolic risk and increased mortality rates. Considering that the vast majority of individuals with NAFLD are mainly asymptomatic, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 312 publications
1
25
0
1
Order By: Relevance
“…Unfortunately, FibroScan was not available in this study. However, APRI score could be useful in the diagnosis of fibrosis in the primary care, as it appears to increase with a higher METAVIR score (biopsy scale for liver fibrosis) and its AUROCs for predicting significant fibrosis were 0.87 (95% CI, 0.79–0.95) [ 60 , 61 ]. In addition, one European real-world article revealed that patients with liver fibrosis based on transient elastography (liver stiffness ≥ 8 kPa) have higher APRI (0.665 vs. 0.316) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, FibroScan was not available in this study. However, APRI score could be useful in the diagnosis of fibrosis in the primary care, as it appears to increase with a higher METAVIR score (biopsy scale for liver fibrosis) and its AUROCs for predicting significant fibrosis were 0.87 (95% CI, 0.79–0.95) [ 60 , 61 ]. In addition, one European real-world article revealed that patients with liver fibrosis based on transient elastography (liver stiffness ≥ 8 kPa) have higher APRI (0.665 vs. 0.316) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, instead of using quantitative measurement of steatosis, such as controlled attenuation parameter, we used ultrasound for NAFLD diagnosis, which were more reliable when more than 33% of hepatocytes are steotatic. However, ultrasound bares high diagnostic accuracy and had been strongly recommended as a first-line image in patients with suspected NAFLD [ 60 ]. Fourth, we were not able to obtain participants’ portion of high-purine diet, which were largely related to hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…SIRTs are a potential therapeutic target for NAFLD as they protect hepatocytes against lipotoxicity [ 246 ]. The current state of sirtuin-targeted drug discovery and development has been recently reviewed in [ 248 , 249 ]. Small molecule sirtuin regulators have been developed, with a few compounds targeting human SIRTs still being in clinical development.…”
Section: Nafld Treatmentsmentioning
confidence: 99%
“…Specifically, for nonbariatric and bariatric patients, it has obtained better results that APRI, showing an AUROC of 0.83 and 0.81, respectively [17 ▪▪ ]. Furthermore, some researchers described the ELF score, showing in a recent systematic review and meta-analysis to have a sensitivity of >90% for excluding fibrosis in NAFLD patients [22 ▪▪ ,43]. Other models such as the Fibromax, which combines five components into one algorithm, is considered an accurate score for liver fibrosis [44].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, one of the most recent efforts to use ‘-omics’ approaches has been devoted to identify new biomarkers of NAFLD, NASH and advanced fibrosis [48]. These techniques include proteomics, transcriptomics, metabolomics, genomics and other novel markers such as the bacterial microbiome involving metagenomics [22 ▪▪ ]. Recent studies have shown that there are differences in protein expression between patients with NAFLD and healthy controls [48].…”
Section: Introductionmentioning
confidence: 99%